The effect of ageing on recollection: the role of the binding updating process. Issue 9 (20th October 2016) - Boujut, Arnaud; Clarys, David
ABSTRACT: The aim of this study was to highlight the underlying process responsible for the age-related deficit in recollection. Through two experiments using the Remember-Know-Guess procedure (Gardiner, J. M., & Richardson-Klavehn, A. [2000]. Remembering and knowing. In The Oxford handbook of memory (pp. 229–244). New York, NY: Oxford University Press) in recognition, we manipulated the opportunity to update bindings between target items and their encoding context, in young and older adults. In the first experiment we impaired the binding updating process during the encoding of items, while in the second we supported this process. The results indicated that the "Remember" responses in the younger group were specifically reduced by the impairment of the binding updating process (Exp. 1), suggesting that this ability is useful for them to encode a specific episode. Conversely, only the "Remember" responses in the older group were improved in accuracy by supporting the binding updating process (Exp. 2), suggesting that their weakness in this ability is the source of their failure to improve the accuracy of their memories. The overall results support the hypothesis that the age-related decline in episodic memory is partly due to a greater vulnerability to interference on bindings, impairing the ability to update content-context bindings as and when events occur.